15. The Crafting of the News: The British Media and the Israel-Palestine Question - Tim Llewellyn (For Palestine: Essays from the Tom Hurndall Memorial Lecture Group, 2023)
Journalism is not a perfect art, a perfect form. News editors are faced everyday with myriad stories. They have to make instant judgements, important stories fall by the wayside and are ignored. Many other things operate to take our interest, which is in Palestine and Israel, out of focus for a while. But the main point I want to make is that when the story is covered, as it is from time to time now, and as it used to be more consistently, it should be covered properly. And my case is that over the past 20 years now, the BBC particularly, but the other broadcast media as well, and to some extent, newspapers which had been sympathetic to the Palestinian cause or Palestinian legitimate aspirations for equal rights, have not done the job properly. As to the BBC, I say this not because I am anti-BBC, and not because I’m a resentful ex-employee. I still admire the BBC. And I think the institution should remain. But it does not do the Israel/Palestine job properly. It listens to the voices of government and it takes into account the voices of pressure groups instead of listening to public opinion, which as we know, steadily over the past 25 years or so, has moved away from open support of Israel and taken, especially in Britain and in Western Europe, the Palestinian cause seriously.